Criticising the Critic: G. T. Vafopoulos on Antreas Karantonis - Kokoris, Dimitris (Estudios Neogriegos. Revista Científica de la Sociedad Hispánica de Estudios Neogriegos, 2021)
Was the chief literary critic of the 1930’s, Antreas Karantonis, spiteful and unfair in his critical texts about the poetry of G.T. Vafopoulos and was Karantonis a critic who adapted to the poetic evolution? The prominent poet of the 1930’s generation has expressed the opinion that Karantonis has been unfair to his poetry but research on the critical texts shows that, besides the negative views, Karantonis also expressed some positive ones regarding Vafopoulos’ poetry. In addition, the constant critical adaptability that comes as a result of the critic’s communication with the shifting poetic codes, and for which Karantonis’ work is reproached by Vafopoulos, could be considered as an essential –perhaps even the most essential– virtue of the dynamic function of critical discourse.